From surviving to thriving: How sleep, physical activity, and diet shape well-being in young adults - Jack R.H. Cooper; Robin S. Turner; Tamlin S. Conner (PLoS ONE, 2025)
Healthy lifestyles are a cornerstone of optimal physical health, yet their contribution to optimal mental health is still an open question. This article investigated the relationships between three key health behaviors—sleep quality, physical activity, and dietary choices—and psychological well-being among young adults ages 17–25, a demographic known for disproportionately low levels of well-being. The research used three datasets: a cross-sectional survey (Study 1, N = 1,032) and two daily diary datasets (Study 2, N = 818; Study 3, N = 236) of young adults living in New Zealand, the United Kingdom, and the United States. Multilevel regression analyses examined how these health behaviors simultaneously and synergistically predicted well-being at the between-person and within-person levels, while controlling for covariates such as age, gender, socioeconomic status, and depressive symptoms. Additionally, Study 3 incorporated wearable device-measured physical activity to supplement self-report measures. The findings highlighted better sleep quality as the strongest predictor of well-being across all three datasets, followed by fruit and vegetable consumption, with significant associations between these health behaviors and well-being observed at the between-person and within-person levels. Physical activity also emerged as a reliable predictor of well-being, mostly at the within-person level. The use of device-measured physical activity confirmed similar patterns, reinforcing the validity of findings. Pathways linking health behaviors to well-being were mostly additive, except for a buffering pattern observed at the within-person level indicating that higher fruit and vegetable intake could potentially mitigate the negative impact of poor sleep on daily well-being. This article underscores the importance of the “big three” health behaviors in well-being among young adults, offering insights for future health interventions to improve positive psychological functioning in this population.